2015
DOI: 10.1016/j.hrtlng.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Disease knowledge, perceived risk, and health behavior engagement among adolescents and adults with congenital heart disease

Abstract: Objective Survivors of congenital heart disease (CHD) are at risk for life-threatening complications as they age. This study aimed to examine the association of knowledge of future health risks, perceived risk, and health behaviors among adolescents and adults with CHD. Methods CHD survivors (N=199, ages 15–39; 23% simple, 44% moderate, 33% complex lesions) completed measures of risk knowledge accuracy and perceived risk for developing complications, and reported physical activity and saturated fat intake. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Several factors may contribute to the identified differences between age groups. First, as participants age, their disease knowledge, including knowledge about future health risks as a consequence of having CHD, may improve 24 . Having a better understanding of the risks present may contribute to perceived stress and emotional distress, though this has yet to be empirically tested.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may contribute to the identified differences between age groups. First, as participants age, their disease knowledge, including knowledge about future health risks as a consequence of having CHD, may improve 24 . Having a better understanding of the risks present may contribute to perceived stress and emotional distress, though this has yet to be empirically tested.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously published that similar educational programs sustained over a period of 4-6 months do, in fact, result in sustained improvements in heart disease risk profiles, a reduction in inflammatory burden, and cardiometabolic risk in racial/ethnic minority women. 6,20,42 In addition, others have demonstrated that awareness translates to action and poor health behaviors translate to physical health disorders, 44 pointing to the importance of awareness and knowledge as an important factor in the path to improved physical health. It is unclear as to what extent baseline knowledge predicted change in knowledge in our study, and whether the gains observed were, in part, attributable to lower baseline knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first report of NA undertaken in adults with CHD. It adds depth of detail and context to the existing quantitative literature regarding transition, disease knowledge, psychiatric disorders and physical limitations in this population . Addressing these nonsurgical, lifespan challenges is increasingly important as the distribution of complex CHD shifts from pediatric to adult practice .…”
Section: Discussionmentioning
confidence: 99%
“…It adds depth of detail and context to the existing quantitative literature regarding transition, 5-7 disease knowledge, psychiatric disorders and physical limitations in this population. [8][9][10][11][12] Addressing these nonsurgical, lifespan challenges is increasingly important as the distribution of complex CHD shifts from pediatric to adult practice. 2 It makes sense to inform our efforts with voices of "expert witnesses".…”
Section: Discussionmentioning
confidence: 99%